TINJAUAN HUKUM ISLAM TERHADAP PRAKTEK HUTANG PIUTANG MELALUI MEDIA APLIKASI GOJEK PADA PENGGUNA GOPAYLATER (AN NUQUD, 2023)
Lending and borrowing in this millennial era is not limited to face-to-face. The emergence of FinTech makes it easy for people to transact with various products, one of which is online credit. With online credit, people can shop now and pay later with the PayLater feature. The PayLater feature is widely used by various platforms, one of which is Gojek with its GoPayLater. The research method used is library research, which is a research approach that uses published sources of information such as books, journal articles, reports and other documents as the main basis for collecting data and analyzing it. This research is also called secondary data research. In the Gojek application, it imposes excessive interest or additional fees in loan transactions because additional costs exceed the principles of justice and without any valid justification, this can be considered as usury which is contrary to Islamic law